Periodontitis and multiple markers of cardiometabolic risk in the fourth decade: A cohort study. Issue 6 (30th August 2018) - Shearer, Dara M.; Thomson, W. Murray; Cameron, Claire M.; Ramrakha, Sandhya; Wilson, Graham; Wong, Tien Yin; Williams, Michael J. A.; McLean, Rachael; Theodore, Reremoana; Poulton, Richie
Abstract: Objectives: To examine associations between periodontitis at ages 32 and 38 and a range of early cardiometabolic risk biomarkers at age 38. Methods: Periodontal probing depth and bleeding on probing data collected during the age‐32 and age‐38 assessments in the Dunedin Multidisciplinary Health and Development Study were used to quantify periodontal inflammatory load. Retinal microvascular abnormalities, endothelial dysfunction, and metabolic syndrome data were collected during the age‐38 assessment. Regression models were used to examine associations between these cardiometabolic risk markers and (1) the inflammatory load at age 38 and (2) the change in inflammatory load between ages 32 and 38. Results: Periodontal inflammatory load was recorded for 890 Study members at age 32, 891 at age 38, and 856 at both ages. Retinal vessel data were available for 922, endothelial dysfunction data for 909 and metabolic syndrome data for 905 at age 38. Neither the inflammatory load of periodontitis at 38 nor the changes in inflammatory load 32‐38 were found to be associated with any of the three cardiometabolic risk markers. Conclusions: Periodontitis was not associated with markers of cardiometabolic risk at this relatively early stage in the life course. It is possible that any influence of periodontitis on cardiometabolic health develops later in life, or periodontitis is not involved in the putative causal chain comprising systemic inflammation, cardiometabolic risk markers, and subsequent cardiovascular risk.